Ziyadah and Hadzf: The Dynamics of Addition and Omission in Philological Studies - Siti Nurkholisoh; M. Hadi Masruri (HISTORICAL: Journal of History and Social Sciences, 2025)
This study examines the phenomena of ziyadah (addition) and hadzf (omission) in classical Arabic manuscripts, which are central elements in understanding the dynamics of texts. In the historical context of copying, this phenomenon is not only related to writing techniques, but also reflects the cultural and social conditions in which the text was written. The purpose of this study is to emphasize the importance of the study of ziyadah and hadzf in understanding the changing meaning and context of the text. The method used is a descriptive qualitative approach with text analysis, which includes the collection of data from classical texts and philological literature, as well as concrete analysis of examples of ziyadah and hadzf. The results of the study show that the addition and omission of elements in texts can affect the interpretation and public acceptance of these works. In addition, this study underscores the need for a critical methodology in analyzing and documenting text changes in order to maintain the integrity and authenticity of classical manuscripts. Thus, a deeper understanding of ziyadah and hadzf can enrich the study of the literature and history of the Arab world, as well as provide a more comprehensive insight into the influence of classical texts on the development of culture and thought in the Islamic world.